IFN-λ: A New Inducer of Local Immunity against Cancer and Infections - Lasfar, Ahmed; Zloza, Andrew; de la Torre, Andrew; Cohen-Solal, Karine A. (Frontiers in Immunology, 2016)
IFN-λ is the newly established type III IFN with unique immuno-modulatory functions. In contrast to the IFN- family and to some extent IFN-, IFN-λ acts in specific areas of the body to activate resident immune cells and induce local immunity, and is instrumental in preventing infections and keeping transformed cells under control. Mucosal areas of the lung and gastrointestinal tract are now under scrutiny in the elucidation of the immune mechanisms triggered by IFN-λ. New evidence also indicates the crucial role of IFN-λ in promoting viral protection and inducing innate immunity against solid cancers. Based on its unique biological activities among the members of the IFN system, new immunotherapeutic approaches centered around IFN-λ are now emerging for the treatment of cancer, infection, and autoimmune diseases. In the present review, we highlight the recent advances involving IFN-λ immuno-modulatory functions. We also discuss the potential of utilizing IFN-λ as a therapeutic agent.